For Now and Forever (The Inn at Sunset Harbor-Book 1) - Sophie, Love (Lukeman Literary, 2016)
"Sophie Love's ability to impart magic to her readers is exquisitely wrought in powerfully evocative phrases and descriptions....FOR NOW AND FOREVER is the perfect romance or beach read, with a difference: its enthusiasm and beautiful descriptions offer an unexpected attention to the complexity of not just evolving love, but evolving psyches. It's a delightful recommendation for romance readers looking for a touch more complexity from their romance reads." --Midwest Book Review (Diane Donovan) "FOR NOW AND FOREVER is a very well written novel, describing the struggle of a woman (Emily) to find her true identity. The author did an amazing job with the creation of the characters and her description of the environment. The romance is there, but not overdosed. Kudos to the author for this amazing start of a series that promises to be very entertaining." --Books and Movies Reviews, Roberto Mattos Emily Mitchell, 35, living and working in New York City, has struggled through a string of failed relationships. When her boyfriend of 7 years takes her out for their long-awaited anniversary dinner, Emily is sure that this time will be different, that this time she will finally get the ring. When he gives her a small bottle of perfume instead, Emily knows the time has come to break up with him-and for her entire life to have a fresh start. Reeling from her unsatisfying, high-pressure life, Emily decides she needs a change. She decides on a whim to drive to her father's abandoned home on the coast of Maine, a sprawling, historic house where she'd spent magical summers as a child. But the house, long-neglected, is in dire need of repair, and the winter is no time to be in Maine. Emily hasn't been there in 20 years, when a tragic accident changed her sister's life and shattered her family. Her parents divorced, her father disappeared, and Emily was never able to bring herself to step foot in that house again. Now, for some reason, with her life reeling, Emily feels drawn to the only childhood place she ever knew. She plans on going just for a weekend, to clear her head. But something about the house, its numerous secrets, its memories of her father, its oceanfront allure, its small-town setting-and most of all, its gorgeous, mysterious caretaker-doesn't want to let her leave. Can she find the answers she's been looking for here, in the most unexpected place of all? Can a weekend become a lifetime? FOR NOW AND FOREVER is book #1 in the debut of a dazzling new romance series that will make you laugh, make you cry, will keep you turning pages late into the night-and will make you fall in love with romance all over again. Book #2 will be available soon.
Keywords: Romantika, romány pro ženy